Internalization of ferromagnetic nanowires by different living cells - PRINA MELLO, ADRIELE; COEY, JOHN (My University, 2006)
The ability of living cells, either adherent or suspended, to internalize nickel nanowires is demonstrated for MC3T3-E1, UMR106-tumour and Marrow-Stromal cells. Nanowires were produced by electrodeposition, 20 mum long and 200 nm in diameter. Cell separation and manipulation was achieved for the three cell types. Applied magnetic field successfully oriented the internalized nanowires but no clear anisotropy is induced on the adherent cells. Nanowires tend to bind to cytoplasm metalloproteins and trigger lysosome reorganization around the nucleus. This work demonstrates the applications of nanowires in adherent and suspended cells for cell separation and manipulation, and further explore into their role in nanobiotechnology.
PUBLISHED
Keywords: nanowires; Nanoscience & Materials